(3eNJUQ GdHQgGfs - (3eLghds; (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3Gddg CMeO hEjGg ChMO hYdjg hYdi CUMGHg CUdi hGSLO CeG HYO (B: (3agPG GdcJGH hGdHQgGf aQSGQgGf cdGgeG Nje ai HMHhMI GdaGUMI hWfH , agPG ChLR hPGc GdWfH hHCSeg jSJaJM s
(3BNQgG (B:s
(3GddaX GdChd hGdfSN HjGf EfJaGA GdTQW GdebOQ ebGQfkG ddaX eeG HGdhVY hdcf HGdhbGYO ced hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjO GdeQSdjf hNGJe GdfHjjf hQVi Gddg Yf GdNdaGA GdQGTOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(676/2) s
Keywords: (3CUhd Gdabgs